Strategi Komunikasi dan Pelayanan Kader Kesehatan terhadap Pencegahan Penyakit Menular pada Komunitas Suku Anak dalam di Kabupaten Batanghari Provinsi Jambi - Listautin Listautin; Nia Nurzia (Universitas Batanghari Jambi, 2020)
Indonesia as Tropical Country is an endemic area for various infectious diseases, such as malaria, tuberculosis (TBC), Acute Respiratory Infections (ARI), diarrhea, Dengue Hemorrhagic Fever (DHF), skin diseases, hepatitis and so on. One popular tribe in Indonesia, known as Suku Anak Dalam, they haveunique behavior such as closed-minded, stubborn and fanatical about old custom. The number of infectious diseases of SukuAnakDalam is quite high, the highest is ARI about 34% of total population, malaria is about 33% of the population, skin disease about 29.8% of the population, and hepatitis 23% of 325 population. The purpose of this study is to determine the effect of communication strategies and cadre services toward the prevention of infectious diseases in Suku Anak Dalam Batanghari. This research is analytic research, quantitative approach. The research design is quasi-experimental design using Time series design, pre-test and post-test measurements. The design of this study uses only one group, without control group. The population of this research is Suku Anak Dalam community, either male or female adult with the total number is about 325, and the samplesare 74 respondents. The hypothesis test used is comparative hypothesis test, T-test paired (Wilcoxon). Statistical test results show that p-value <0.005 means that there are differences between the educational outcomes of communication strategies and pre-test and post-test of health cadre services. It can be concluded that there is an effect of communication strategies and health cadre services toward the prevention of infectious diseases. The efforts that can be applied such as teaching cadres about the prevention of infectious diseases and intense way of therapeutic communication therefore health cadres can provide information and provide services to Suku Anak Dalam community easily.